(untitled) (Entrepreneurship Journal for Finance and Business, 2025)
The role of small and medium enterprises is essential in economic and social development and is the focus of attention of governments and international organizations, most notably the United Nations Industrial Development Organization. Their importance increases in developing countries because they represent the only realistic prospects for economic development and an effective tool for addressing the problem of unemployment and poverty there. The research aims to clarify the concept of small and medium enterprises and their role in achieving comprehensive economic and social development in Iraq in the current and future stages. The descriptive and deductive approaches were followed, in an attempt to link small and medium enterprises and sustainable development in the Iraqi economy in this research. Small and medium enterprises face a number of obstacles that limit their contribution and effectiveness in sustainable development in Iraq, then explaining the most important details in order to develop appropriate solutions for them. In this research, we will focus on several concepts for small and medium enterprises and shed light on the most important conclusions, including that the private sector of small and medium enterprises is in dire and necessary need of government support to be able to advance and develop. In conclusion, a number of recommendations were presented for the development of small and medium enterprises, and we hope that they will be of assistance in the research topic, including the urgent need for the Iraqi government to play an important role in creating supportive regulatory frameworks through collective funds and other mechanisms, establishing microfinance units in the Ministry of Trade and the Central Bank of Iraq to provide the necessary consultations for the work of small projects.